Julija je stopila v "cerkev razsvetljeno" - Bjelčevič, Aleksander (Slavistična revija, 2013)
Prešeren scholars have provided different answers to the question of when Prešeren fell inlove with Julija Primic. Some suggest it happened in 1831, while others believe it happened in1833, following Prešerens mention of that year in the sonnet Je od veselga časa teklo leto.Those who suggest the year 1831 must explain the meaning of the story in the sonnet about the Easter encounter in the Trnovo church. Many consider the Petrarchan story a fabrication. However, in 1906, Avgust Žigon wrote that the sonnet describes two actual events: In 1833, Prešeren revives the memory of the first meeting in 1831. Kidrič's convincing refutation of Žigons idea stood until 1939, when Grafenauer noted that the church was darkened on Easter Saturday, and not illuminated (razsvetljena), as is written in the sonnet. This was a key supporting argument for Žigons thesis. The author shows in the article that Grafenauer was mistaken.
Keywords: Easter; Grafenauer, Ivan, 1880-1964; interpretacije; interpretation; Prešeren, France, 1800-1849; Public holidays in Slovenia; Slovene literature; Slovene poety; slovenska književnost; slovenska poezija; sonet; sonnet; velika noč; Žigon, Avgust, 1877-1941